1989
DOI: 10.1111/j.1752-1688.1989.tb03095.x
|View full text |Cite
|
Sign up to set email alerts
|

HEDONIC PRICE ANALYSIS OF THE EFFECT OF A FLOODPLAIN ON PROPERTY VALUES1

Abstract: The effect of a floodplain location on the market value for property is controversial, with the conventional wisdom being that buyers are myopic. Previous parametric and nonparametric statistical tests have proven inconclusive in deciding the issue. Herein, a theoretical model, that of hedonic price indexes, is posited and tested, using housing sales characteristics data obtained from a Multi‐List Service cooperative. This study suggests that home buyers do adjust the purchase price for houses within a floodpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 20 publications
4
30
0
2
Order By: Relevance
“…This finding is consistent with international studies (Bartosova et al, 1999;Bin and Kruse, 2006;Donnelly, 1989;Guofang et al, 2003;Speyrer and Ragas, 1991;Thompson and Stoevener, 1983). Furthermore, for our case study we show that for every vertical metre a property is below the 100-year ARI mark, additional discounting applies.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with international studies (Bartosova et al, 1999;Bin and Kruse, 2006;Donnelly, 1989;Guofang et al, 2003;Speyrer and Ragas, 1991;Thompson and Stoevener, 1983). Furthermore, for our case study we show that for every vertical metre a property is below the 100-year ARI mark, additional discounting applies.…”
Section: Discussionsupporting
confidence: 94%
“…The mean price of a home in their sample was US$100,000. It is also worth noting that Donnelly (1989) finds that in LaCrosse, Wisconsin, location within a floodplain reduced residential prices by an average of about US$6,000, with the average property in the region standing at about US$50,000.…”
Section: Prior Researchmentioning
confidence: 99%
“…Regarding the use of HPM for the assessment of the impact of flood risk and coastal hazards on housing values, an evolution of the focus put in the analyses can be noted that initially took into account only the localization in floodplains and subsequently, started analyzing also interactions between flood risk and environmental amenities (e.g., views on rivers and coastlines) often using spatial hedonic models. Donnelly [37] in 1989 observed that previous studies showed a controversial effect of a floodplain location on the real estate market value because of buyers being "myopic" [37]. Using housing sales from a small Midwestern town in which severe flooding had occurred one decade before his analysis, he demonstrated that homebuyers did adjust the purchase price for houses within a floodplain by an amount of, on average, over 12%.…”
Section: The Use Of Hedonic Approach For the Assessment Or Urban Qualitymentioning
confidence: 99%